The relationship between cyberloafing and task performance at Majlis Perbandaran Teluk Intan, Perak, Malaysia / Nurul Suhaida Mazlan - Mazlan, Nurul Suhaida (2014)
Misusing the internet at work for non-work related purposes or cyberloafing has become a worrisome phenomenon in organizations (Faridahwati,2013). This is because cyberloafing at workplace may become destructive towards employee task performance. This study is to identify factor by cyberloafing at Majlis Perbandaran Teluk Intan (MPTI). Throughout the study, it involves with three factors that are Attitudes, Organization Policy and Social Norms. Data are gained through survey which conducted about four months with 104 samples using Krejeie and Morgan Sampling Size. Objective of this study is to identify factor contribute to employee's cyberloafing at Majlis Perbandaran Teluk Intan,Perak, therefore the Pearson product moment correlation analysis is used.